Addition of Blood Pressure and Weight Transmissions to Standard Remote Monitoring of Implantable Defibrillators and its Association with Mortality and Rehospitalization. Issue 5 (May 2017) - Al-Chekakie, M. Obadah; Bao, Haikun; Jones, Paul W.; Stein, Kenneth M.; Marzec, Lucas; Varosy, Paul D.; Masoudi, Frederick A.; Curtis, Jeptha P.; Akar, Joseph G.
Abstract : Background—: Among patients with implantable defibrillators (ICD), use of remote patient monitoring (RPM) is associated with lower risk of death and rehospitalization. Standard ICD RPM can be supplemented with weight and blood pressure data. It is not known whether standard RPM plus routine weight and blood pressure transmission (RPM+) is associated with better outcomes. Methods and Results—: RPM+ patients (n=4106) were compared with patients who only transmitted standard ICD RPM data (n=14 183). Logistic regression models identified patient, physician, and hospital characteristics associated with RPM+ utilization. Mortality and rehospitalization were examined using landmark analyses at 180 days after ICD implant in Medicare fee-for-service patients. In these analyses, we examined the independent association between RPM+ utilization and times to events up to 3 years after device implantation with Cox regression models. We further examined whether the association between RPM+ and outcomes varied by frequency or type of transmissions. Determinants of RPM+ utilization included impaired ejection fraction, cardiac resynchronization therapy, and institutional practice. The risk of mortality of RPM+ patients was similar to standard ICD RPM patients (hazard ratio, 1.06; 95% confidence interval, 0.94–1.19; P =0.34). RPM+ patients also had similar risks of all-cause hospitalization (subdistribution hazard ratio, 1.03; 95% confidence interval, 0.94–1.14; P =0.52), cardiovascular hospitalization (subdistribution hazard ratio, 0.92; 95% confidence interval, 0.83–1.02; P =0.15), or heart failure hospitalizations (subdistribution hazard ratio, 0.90; 95% confidence interval, 0.78–1.05; P =0.18). RPM+ transmission frequency was not associated with outcomes. Conclusions—: In patients using standard ICD RPM, the added transmission of weight and blood pressure data was not associated with improved outcomes. Abstract : Supplemental Digital Content is available in the text.